2017
DOI: 10.21037/atm.2017.06.55
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous breathing: a double-edged sword to handle with care

Abstract: In acute hypoxemic respiratory failure (AHRF) and acute respiratory distress syndrome (ARDS) patients, spontaneous breathing is associated with multiple physiologic benefits: it prevents muscles atrophy, avoids paralysis, decreases sedation needs and is associated with improved hemodynamics. On the other hand, in the presence of uncontrolled inspiratory effort, severe lung injury and asynchronies, spontaneous ventilation might also worsen lung edema, induce diaphragm dysfunction and lead to muscles exhaustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 52 publications
0
56
1
3
Order By: Relevance
“…The monitoring of pulmonary pressures through the usual pressure curves shown by ventilators during weaning is mixed by the presence of spontaneous ventilation. The pressures abolished by the effect of the BNM appear after their withdrawal and can influence the lung lesion as well as during the transition from controlled to spontaneous [ 70 , 72 ]. Amato et al in a large retrospective analysis showed the increase in DP as a worse predictor of outcome in patients with ARDS [ 56 ].…”
Section: Potential Methods For Predicting MV Weaning In Ardsmentioning
confidence: 99%
“…The monitoring of pulmonary pressures through the usual pressure curves shown by ventilators during weaning is mixed by the presence of spontaneous ventilation. The pressures abolished by the effect of the BNM appear after their withdrawal and can influence the lung lesion as well as during the transition from controlled to spontaneous [ 70 , 72 ]. Amato et al in a large retrospective analysis showed the increase in DP as a worse predictor of outcome in patients with ARDS [ 56 ].…”
Section: Potential Methods For Predicting MV Weaning In Ardsmentioning
confidence: 99%
“…Patients who receive no sedation may breathe spontaneously during ventilation 22,23 . To support such events, the ventilator must be able to recognise the patient's breathing effort, so that they can trigger and/or cycle the inspiration phase themselves.…”
Section: Patient-triggered/patient-cycled Ventilationmentioning
confidence: 99%
“…Spontaneous negative-pressure breathing depends on the generation of a pressure gradient between the atmosphere and the alveoli, wherein the respiratory muscles create a "negative pressure" in the thorax to facilitate the flow of air from the higher pressure atmosphere to the lower pressure alveoli. 74 Thus, Pres is the difference between the peak and plateau pressures in the inspiratory hold maneuver, while Pel is the difference between the plateau and PEEP. Resistance and compliance can be derived from pressure pre-set modes, in a slightly more complex manner.…”
Section: Positive Pressure Ventilation During Obstructive Lung Diseasmentioning
confidence: 99%